Expanding Access to the aservic Spiritual Competencies through a Spanish Translation - Vinces-Cua, Jennifer D. (Counseling and values, 2023)
Understanding the mechanisms and competencies of incorporating religion and spirituality in the Latinx community for mental health is key to detangling the nuances of coping within this fast-growing community. Hence, it is important for counselors who work with bilingual clients and address spiritual and religious matters in counseling to access the Spanish version of the aservic (Association for Spiritual, Ethical, and Religious Values in Counseling) Competencies. This article outlines the translation process to make these available to counselors and counselor educators.